2014
DOI: 10.1039/c3cc49000a
|View full text |Cite
|
Sign up to set email alerts
|

A simple route to azaborinylphosphines: isoelectronic B–N analogues of arylphosphine ligands

Abstract: Azaborinylphosphines are readily prepared by the reaction of silylphosphines with a chloroborane under mild conditions; they are shown to contain P-B bonds that are sufficiently robust to allow these ligands to be used in homogeneous catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 15 publications
(9 reference statements)
1
13
0
Order By: Relevance
“…Phosphinoboranes have been shown to heterolytically cleave H 2 ,2 dehydrogenate amine‐boranes3 and react with compounds containing CN, CO and CC functionalities 4. Furthermore, they have the capacity to ligate as κ 1 ‐P1a or η 2 ‐P=B5 and we have shown that they can be ligands for efficient homogeneous alkene hydrogenation catalysis 6…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Phosphinoboranes have been shown to heterolytically cleave H 2 ,2 dehydrogenate amine‐boranes3 and react with compounds containing CN, CO and CC functionalities 4. Furthermore, they have the capacity to ligate as κ 1 ‐P1a or η 2 ‐P=B5 and we have shown that they can be ligands for efficient homogeneous alkene hydrogenation catalysis 6…”
Section: Methodsmentioning
confidence: 79%
“…The borylphosphine L 1 was prepared in quantitative yield from the chlorosilane elimination reaction6, 17 shown in Scheme ; L 1 has been fully characterised (see the Supporting Information for the data), including its 31 P NMR spectrum, which shows a signal at −48.4 ppm that is broad ( w 1/2 =67 Hz) due to unresolved coupling to quadrupolar 11 B. Treatment of L 1 with one equivalent of Me 3 NO (TMAO) led to complete conversion to a product assigned structure L 2 on the basis of the following NMR data.…”
Section: Methodsmentioning
confidence: 99%
“…The trans-[RhCl(CO)(L) 2 ] (L = 21a,b or 68a,b), which are the azaborinyl complexes 69a,b and their organophosphorus analogues 70a,b (Scheme 28) were found to be isostructural in the solid state [46]. Electronically however, the Rh CO stretching frequencies showed that the P B N ligands 21a,b ( (CO) = 1951 cm −1 (21a) and 1946 cm −1 (21b)) are more electrondonating than their P C C counterparts 68a,b ( (CO) = 1966 cm −1 (68a) and 1951 cm −1 (68b)).…”
Section: Rhodium Complexesmentioning
confidence: 98%
“…(iii) Me 3 SiCl elimination Borylphosphines 21 and 36 featuring aromatic BN-containing heterocycles have been prepared by the reactions of chloroboranes with silylphosphines (Scheme 10) [46,63]. The efficiency of this route under mild conditions has been associated with the aromaticity of the boryl fragment.…”
Section: (Ii) B-nucleophilementioning
confidence: 99%
See 1 more Smart Citation